Strategi Diplomasi Indonesia Dalam Menjaga Kedaulatan Maritim di Laut Natuna Utara (Perspekstif Teori Mandala) - Azwan Rifa'i; Suherry Suherry; Alfi Husni; M.Dwiki Akbar; Tomi Hamdan (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
As the largest archipelagic country in the world, Indonesia has a strategic interest in maintaining its maritime sovereignty, especially in the North Natuna Sea area which is rich in natural resources and has high geopolitical value. This area faces threats from China's unilateral claims through the Nine-Dash Line policy which is contrary to the principles of UNCLOS 1982 and disrupts Indonesia's Exclusive Economic Zone (EEZ). This study aims to analyze Indonesia's diplomatic strategy in maintaining sovereignty in the region using the Mandala theory perspective. The Mandala theory, which originates from the traditional Asian power system, offers a conceptual framework that places the state as the center of power with a layered circle of influence. This study uses a qualitative method through a literature review approach by analyzing various academic sources, government policies, and scientific news data. The results of the study show that Indonesia's diplomatic strategy includes strengthening power (Mandala Inti), forming a central regional alliance (Sandhi), an active free neutral stance (Asana), and the duality of hard and soft strategies (Dvaidhibhava). The integration of the active free diplomacy approach and the Mandala theory allows Indonesia to implement an adaptive, contextual, and local value-based foreign policy in the face of geopolitical pressure. This study contributes to the development of Indonesian diplomacy studies by enriching theoretical perspectives through non-Western approaches that are relevant to the character of the Southeast Asian region.